PENGARUH PERTUMBUHAN EKONOMI DAN TINGKAT UPAH TERHADAP TINGKAT PENGANGGURAN MELALUI JUMLAH INVESTASI DI PROVINSI JAMBI - Murniati, murniati - (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2018)
This study aims to determine the direct influence between economic growth and wage rates on the amount of investment in Jambi Province and to know the direct influence between economic growth, wage rate and amount of investment on unemployment rate in Jambi Province. And than to determine the indirect effect of economic growth, the level of wages on the unemployment rate through the mediation of investment in Jambi Province. The data used is secondary data and use analysis path. From the research results obtained conclusion as follows: 1. a. Economic growthÂ Â  (X1) has a significant effect on the investment with t count > t table ie 13,573 > 2,447. b. Wage rate (X2) has significant effect with t count > t table ie 32,026 > 2,447. 2. a. Economic growth (X1) has no significant effect on unemployment rate (Y2) because the value of t arithmetic <t table is -2.818 < 2.571. b. Wage rate (X2) has no significant effect on unemployment rate (Y2) because the value of t arithmetic < t table is 2,159 < 2,571. c. The amount of investment (Y1) does not significantly affect the unemployment rate (Y2) because the value of t arithmetic < t table is 2,284 < 2.571). 6. There is indirect influence between economic growth, wage level to unemployment rate through mediation of investment amount in Jambi Province, because z count> z table.